Adenoid Hypertrophy in Adults and Nasal Obstruction - Hamad, aKhalid D.; Alhamad, Raghdan M.D.; Jassim, aAnmar A. (AL-Kindy College Medical Journal, 2014)
Background .To know the incidence of adenoid hypertrophy in adults causing nasal obstruction and other nasal complains. Methods.Prospective studyof(140 ) adult patientstheir main chief complaint were nasal obstruction , presented to Otolaryngology department at Aljumhory Teaching Hospital in Mosul , from the period (september 2010 to september 2011) ,their age ranged from (21 to 53) years . They were investigated clinically, radiologicaly ,and nasal endoscopic examination was carried out (rigid and fibro-optic ) . Adenoidectomy was performed for those with adenoid hypertrophy and sent for histopathological study . Results:. we found adenoid enlargement in(24) patients (17.14%),in addition to nasalobstruction they were also complaining of Post nasal discharge (19) patients, followed by snoring (17) patients , headache and facial pain (15) patients, deafness and tinnitus (8) patients and other rhinologicalsymtoms. The patients were followed up for a period ranged from (4 -16) months. We found that (91.6%) were relieved of their nasal obstruction, (82.3%) were relieved from snoring . Other nasal symptoms ; post nasal discharge, headache and facial pain, sore throat and tonsillitis, deafness , tinnitus ,rhinorrhia, Rhinolaliaclausa, otalgia were improved in (68.4% - 50%). Conclusions:Nasal obstruction ,snoring ,post-nasal discharge ,and aural symptoms were often caused by adenoid enlargements in adults . Because the examination of the nasopharynx was inadequate ,many cases of enlarged adenoid were misdiagnosed. Adenoid enlargements in adults should always borne in mind as a cause of nasal obstruction and other rhinological symptoms. Nasal endoscopic examination including the nasopharynx should be done for proper diagnosis.